Impact of smoking, alcohol consumption, and NSAID use on risk for and phenotypes of eosinophilic esophagitis. Issue 1 (27th September 2017) - Koutlas, N T; Eluri, S; Rusin, S; Perjar, I; Hollyfield, J; Woosley, J T; Shaheen, N J; Dellon, E S
Summary: There are few data exploring modifiable risk factors for eosinophilic esophagitis (EoE). We aimed to determine if smoking, alcohol consumption, and nonsteroidal anti-inflammatory drug (NSAID) use were risk factors for EoE, and to assess their impact on EoE phenotypes and treatment outcomes. We performed a case-control study analyzing data collected from a prospective cohort of adults undergoing upper endoscopy for symptoms of esophageal dysfunction. Incident EoE cases were diagnosed via consensus guidelines. Exposure data were collected via standardized patient questionnaire. Follow-up assessments for cases were made after treatment, with histologic response defined as <15 eosinophils per high-power field (eos/hpf). Exposures were compared between EoE cases and controls, among EoE cases with and without fibrostenosis, and among EoE responders and nonresponders. A total of 115 cases and 225 controls were analyzed. Cases were less likely to have ever smoked cigarettes (23% vs. 47%, P < 0.001) or currently use NSAIDs (17% vs. 40%, P < 0.001) compared to controls. These relations persisted after multivariate analysis. Although alcohol use was more common among cases (75% vs. 51%, P < 0.001), the effect was abrogated after multivariate analysis. Smoking, alcohol, and NSAID use were not associated with the fibrostenotic phenotype. There was a trend toward improved histologic response among EoE patients concomitantly using NSAIDs (87% vs. 63%, P = 0.08; aOR 6.97 (95% CI: 0.81–60.3). In conclusion, NSAID and smoking were inversely associated with EoE compared to endoscopy-based controls. Alcohol use was more prevalent in the EoE cases, although not an independent risk factor. Concomitant NSAID use may improve treatment response and is worthy of future study.